2020
DOI: 10.3390/ma13122836
|View full text |Cite|
|
Sign up to set email alerts
|

Alternative to Nitric Acid Passivation of 15-5 and 17-4PH Stainless Steel Using Electrochemical Techniques

Abstract: Increasingly stringent environmental regulations in different sectors of industry, especially the aeronautical sector, suggest the need for more investigations regarding the effect of environmentally friendly corrosion protective processes. Passivation is a finishing process that makes stainless steels more rust resistant, removing free iron from the steel surface resulting from machining operations. This results in the formation of a protective oxide layer that is less likely to react with the environment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 51 publications
2
36
0
Order By: Relevance
“…This behavior is present in other research with different materials [24,55], denoting that Rn and Ψ 0 can be considered counterpart parameters to determine corrosion resistance. However, to analyze the type of corrosion, slope parameters divergent from statistical parameters, they cannot be considered mechanistic [84,85]. For this type of alloy, slope parameters should be employed with discretion.…”
Section: Discussionmentioning
confidence: 99%
“…This behavior is present in other research with different materials [24,55], denoting that Rn and Ψ 0 can be considered counterpart parameters to determine corrosion resistance. However, to analyze the type of corrosion, slope parameters divergent from statistical parameters, they cannot be considered mechanistic [84,85]. For this type of alloy, slope parameters should be employed with discretion.…”
Section: Discussionmentioning
confidence: 99%
“…A change in the electrolyte composition (for example, pH and bacteria life) can reduce the corrosion rate in the implant as mentioned by Bhola, et al [ 4 ]. The Ti6Al4V alloy at 48 and 96 h presents stable behavior of the passive film, demonstrating that the electrochemical reactions on the surface of the alloy are in balance [ 44 , 45 ]. This is consistent with Grosgogeat et al [ 46 ], who studied the electrochemical behavior of titanium in near-real clinical conditions and concluded that it is essential to have oxidated layers that are characteristic of a pseudo-stationary state.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used passivating agent to develop such an oxide layer is nitric acid. Lara-Banda et al investigated an environmentally friendly alternative for the passivation of 15-5 and 17-5PH stainless steels based on citric acid [ 1 ]. It could be shown that, for both types of steel, the passive layer formed in citric acid as passivating solution had very similar characteristics to that formed with nitric acid.…”
mentioning
confidence: 99%